18. Internet Audio Products (Update) - Depow, Jim; Klaas, Jim; Wark, Norine (International Review of Research in Open and Distributed Learning, 2003)
The benefits in distance education of collaborative interaction via online, synchronous audio methods have been discussed in previous reports in this series. As the months go by, new software products are continually introduced to the market and existing products updated. In addition, the effect of increased traffic on the software servers is noted. The current report updates some of the series' previous reviews of online audio-conferencing products (i.e., iVisit, NetMeeting, PalTalk, and Yahoo Messenger), selected because they permit conferencing (i.e., interaction between three or more people), are free/ cost-effective, and operate on PC systems of limited capacity. These products are compared with two fully featured educational and commercial products (LearnLinc and VoiceCafé) that provide benchmarks in terms of reliability, technical features, and ease of use.